1970
DOI: 10.1017/s0022029900013030
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of citrate by lactobacilli isolated from dairy products

Abstract: SummaryTwenty-five strains of lactobacilli isolated from dairy products, includingLactobacillus casei, Lactobacillus plantarumandLactobacillus brevisspecies, were grown in semi-defined media and examined for their ability to ferment citrate and produce formate. Of 7 strains ofL. casei, all utilized citrate to varying extents, as did 9 of 10 strains ofL. plantarumand 3 of 8 strains ofL. brevis.L. caseiproduced 19–35% of the theoretical yield of formate from the citrate utilized,L. plantarum0–11% andL. brevis0–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

1971
1971
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 10 publications
(3 reference statements)
1
22
0
1
Order By: Relevance
“…A number of studies have suggested that Lb. casei is able to derive metabolic energy from citrate metabolism, and energy-producing pathways have been proposed based on the genome sequence and metabolic flux analyses (26,27,36). ATP production by acetate kinase plays a pivotal role in these models.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that Lb. casei is able to derive metabolic energy from citrate metabolism, and energy-producing pathways have been proposed based on the genome sequence and metabolic flux analyses (26,27,36). ATP production by acetate kinase plays a pivotal role in these models.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the NSLAB are excluded from utilizing lactose as an energy source. Potential energy sources for NSLAB in ripening cheese include nucleic acids derived from the autolysis of SLAB (Thomas 1986), amino acids (Kieronczyk et al 2001;Kristoffersen 1956), sugars liberated from glycoproteins or glycolipids present in milk (Fox et al 1998;Williams and Banks 1997), and citrate (Branen and Keenan 1977;Campbell and Gunsalus 1944;Fryer 1970;Fryer et al 1970;Starrenburg and Hugenholtz 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Citrate utilization by NSLAB has been the subject of numerous publications. These research efforts have focused on determining the influence of factors such as pH, the presence of monovalent and divalent cations, the presence and absence of a carbohydrate source, the carbohydrate type and the presence of mixed cultures on citrate utilization by NSLAB (Branen and Keenan 1977;Campbell and Gunsalus 1944;Fryer 1970;Fryer et al 1970;Perry and Sharpe 1960;Starrenburg and Hugenholtz 1991;Williams et al 2000). Most of these studies were conducted in complex media such as milk or MRS.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose and citrate degradation pathways proposed for the L. plantarum wild-type strain (NCIMB8826) and LDH-defective strain (TF103). [1], LDH; [2], pyruvate formate-lyase; [3], acetaldehyde dehydrogenase; [4], alcohol dehydrogenase; [5], phosphotransacetylase; [6], acetate kinase; [7], pyruvate oxidase; [8], pyruvate decarboxylase; [9], ␣-acetolactate synthase; [10], ␣-acetolactate decarboxylase; [11], 2,3-butanediol dehydrogenase; [12], nonenzymatic decarboxylation; [13], pyruvate carboxylase; [14], malate dehydrogenase; [15], fumarase; [16], fumarate reductase; [17], malolactic enzyme; [18], citrate lyase; [19], oxalacetate decarboxylase; [20], mannitol-1-phosphate dehydrogenase; [21] (28), and the authors hypothesized the involvement of hydroxyisocaproate dehydrogenase activities. However, we did not detect any hydroxyisocaproate dehydrogenase activity in TF103 cell extracts using several ␣-keto acids as substrates.…”
mentioning
confidence: 99%